Beauchamp Hall : a novel - Steel, Danielle (New York : Delacorte Press, 2018)
"Winona Farmington once dreamed of graduating from college, moving to New York City, and pursuing a career in publishing. Then real life got in the way when she left college and returned to her small Michigan hometown to care for her sick mother"--Book jacket.
Keywords: Television -- Production and direction -- Fiction; Interpersonal relations -- Fiction; Man-woman relationships -- Fiction; Romance fiction